EFFECT OF ANGIOTENSIN-II RECEPTOR ANTAGONIST LOSARTAN AND ITS COMBINATION WITH DIURETICS ON MYOCARDIAL MORPHO-FUNCTIONAL CONDITIONS IN HYPERTENSIVE PATIENTS WITH LEFT VENTRICULAR HYPERTROPHY - S. N. Tolpygina; E. V. Oschepkova; L. M. Sergakova; A. N. Rogoza (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare the effects of long-term therapy with angiotensin-II receptor antagonist losartan, alone or in combination with hydrochlorothiazide, and amlodipine treatment on left ventricular morpho-functional variables and blood pressure (BP) in hypertensive patients.Material and methods. 25 women and 27 men (average age 52,7±1,2 y.o.) with essential hypertension (1-2 grade) and left ventricular hypertrophy (LVH) were included into the study. After 3 week washout period the patients were randomized in 2:1 fashion to receive either losartan (n=34) or amlodipine (n=17). In 17 patients with insufficient response to losartan monotherapy (50-100mg/day) hydrochlorothiazide (12,5mg) was added to losartan (50mg) 4 weeks later. The daily dose of amlodipine was increased from 5 to 10 mg in 10 patients. At baseline and after 24 weeks of treatment 24-h BP monitoring and echocardiography (with evaluation of cardiac chamber dimensions, inter-ventricular septal and posterior wall thickness, left ventricular mass index -LVMI) were performed.Results. 4-week losartan treatment significantly decreased clinic BP (-14,1±2,2/8,2±1,4 mm Hg, p<0,01), mean daily systolic and diastolic BP (-15,1±2,4 mm Hg and -8,9±1,7 mm Hg , p<0,001), mean day-time and night-time BP and systolic and diastolic BP load in 34 patients. Addition of hydrochlorothiazide induced a further decrease of mean night-time BP, pulse BP, improved circadian rhythm and normalized BP in 75% of patients compared with 50% in losartan alone. Significant decrease of clinic BP (-24,1±3,6/15,2±2,3, p<0,01), mean daily systolic and diastolic BP and BP load were noticed at 24 week of amlodipine treatment. Circadian BP rhythm didn’t change; night-time decrease of BP was insufficient. Antihypertensive efficacy was similar in both groups. Losartan, alone or combined with hydrochlorothiazide, caused regression of LVH in all patients, normalized geometry of left ventricle in 33% of patients and improved left ventricular diastolic function in 88,2% of patients. LVMI decreased due to reduction of wall thickness. Changes in LVMI, relative wall thickness and diastolic function in losartan group were greater than those obtained in amlodipine group.Conclusion. Losartan, administered alone or combined with hydrochlorothiazide, has the greater effect on LVH, geometry and diastolic function of left ventricle compared with amlodipine. These results give evidence that losartan has cardioprotective and possibly other pleiotropic effects.